Impact of the Appropriateness of Prophylactic Antibiotics toward Surgical Site Infections in Caesarean Sections in Hospital "X" Semarang - Wijayanti, Christina; Palupi, Dwi Hadi Setya; Ningrum, Vitarani Dwi Ananda (JURNAL KEBIDANAN, 2025)
Caesarean delivery (caesarean section) continues to increase in Indonesia. Surgical Site Infection (SSI) is a serious issue that can increase morbidity and length of hospital stay. The use of prophylactic antibiotics has been proven to prevent the occurrence of surgical site infections (SSI) in caesarean sections. The hospital has established antibiotic use guidelines as the standard for antibiotic therapy and prophylactic antibiotic use in surgical procedures. This study aimed to see how well the use of antibiotics before caesarean sections matched the hospital's guidelines and how this related to the rate of surgical site infections (SSI). The cross-sectional method determined the relationship between the appropriateness of prophylactic antibiotics and the incidence of SSI. The study used retrospective data from caesarean section patients at Hospital "X" Semarang who received prophylactic antibiotics between January 2023 and June 2024. The research results showed no significant relationship (P0.05) between the appropriateness of prophylactic antibiotic use and the incidence of SSI. The data showed that preventive antibiotics (ampicillin-sulbactam and cefazoline injection) were mostly used correctly in several areas: the right antibiotic was chosen 87% of the time, the correct dosage was used 83% of the time, the right way of giving the injection was followed 92.7% of the time, and the correct length of time for the injection was also followed 92.7% of the time. Nonetheless, there are some discrepancies, namely in the timing of post-cesarean antibiotic therapy (94%), and preventive antibiotic administration (57.7%). During that time, the SSI rate was 2.67%.